Spontaneous Intracranial Arterial Dissection - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2007)
A 14 year-old male with intracranial carotid artery dissection had transient neurologic symptoms and no antecedent illness or trauma, as reported from the University of Kentucky. Lexington.